Examination of the performances of youth soccer players in a 20-metre shuttle run test and a treadmill run test - Chia, M.; Aziz, A. R.; Tan, F.; Teh, K. C. (Advances in Exercise and Sports Physiology, 2005)
The purpose of the study was to examine the performances of youth soccer players in a 20m Multistage Shuttle Run Test (MST) and in a Treadmill Run Test (TRT). Participants were 41 youth male soccer players (16.5 +/- 1.1 yrs; 1.71+/-0.50m; 60.3+/-7.5 kg) with two years of competitive playing experience. On two separate occasions, participants completed a Treadmill Run Test (TRT) and a MST to volitional exhaustion. TRT-derived V‹BO2peak were significantly greater than MST-predicted VO2peak using a child-adolescent specific (53.7+/- 6.0 vs. 51.9+/-3.5 ml/kg/min, p<0.05), and correlations between TRT-derived and MST-predicted VO2peak were moderate (r= 0.45 and 0.48, p<0.05). 95 % limits of agreement between TRTderived and MST-predicted VO2peak were -|12.9 to 9.1 ml/kg/min. For the 41 male youth soccer players, TRT VO2peak and MST performance were best described by the equation, Y VO2peak in ml/kg/min) =53.5-0.31 (body mass in kg) +{0.19 (total number of shuttles completed) (R=0.68, SEE=4.9 ml/kg/min). The equation is proposed as more appropriate for predicting VO2peak from MST performance among Asian youth male soccer players but future cross-validation studies are recommended.